(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract Set against the backdrop of early 20th-century America, Theodore Dreiser's "Financier" is a classic examination of ambition, morality, and the complexity of the human condition. With a sharp sense of humor, Dreiser skillfully negotiates the turbulent worlds of finance, power struggles, and moral quandaries via the eyes of the main character, Frank Cowperwood. This abstract explores the complex web of sarcasm and ambition that runs through Dreiser's book, illuminating their meaning and ramifications for comprehending his masterwork.